Identification of potential DAMPs released by necroptosis in estrogen-receptor positive breast cancer cells and their effect on macrophage differentiation - Banita Thakur; Rohit Verma; Aditya Dod; Anil K Ram; Yashwant Kumar; Alka Bhatia (Exploration of Immunology)
Aim: Mutations in key regulators of apoptosis have necessitated exploring the alternative cell death pathways like necroptosis in breast cancer (BC). Necroptosis is immunogenic due to the release of damage-associated molecular patterns (DAMPs) into extracellular environment, which can trigger pro- or anti-tumor immune responses. Inducing necroptosis in estrogen receptor-positive (ER+) BC cells leads to the release of DAMPs, which can influence macrophages polarisation within the tumor microenvironment. The study aims to identify and characterize the DAMPs released from ER+ BC cells after necroptosis induction and to investigate their effects on macrophage properties. Methods: Necroptosis was induced by treating T-47D cells with Z-VAD-FMK and TNF-α (24 hours). The culture medium was collected as induction medium (IM). Necrostatin-1 alongside Z-VAD-FMK and TNF-α was added to inhibit necroptosis, the culture medium was collected as inhibition medium (InM) and used as a negative control for necroptosis. IM also referred as conditioned medium (CM), was analyzed using LC-MS/MS for the identification of DAMPs. THP-1 macrophages were incubated with the CM (24 hours), and their differentiation into M1 or M2 subtypes was assessed using qPCR, by evaluating the expression of specific M1 and M2 markers. Results: A total of 35 unique proteins with potential DAMP activity were identified in the IM. Functional and pathway analyses using PANTHER and DAVID revealed their involvement in immune regulation, metabolism, stress responses, and key pathways such as glycolysis, signaling, and inflammation. These proteins were primarily intracellular or secretory and included cytoskeletal components, chaperones, and binding modulators. Furthermore, IM treatment promoted THP-1 monocyte differentiation into both M1 and M2 macrophage subtypes. Conclusions: These findings highlight the role of necroptosis in generating DAMPs, which can modulate macrophage differentiation within the BC microenvironment. The identified DAMPs hold potential for further investigation as prognostic or predictive biomarkers and therapeutic targets in future studies.